USE OF FLY ASH IN ROADS BUILDING - Goran Tadić; Miladin Gligorić; Aleksandar Došić; Radenko Grujić (Journal of Engineering & Processing Management, 2015)
Fly ash is useful for a variety of applications, because it is a plaster or silicate or aluminosilicate material which is in an isolated form and in the presence of water is combined with calcium hydroxide (from lime, portland cement or dust from furnaces) and formed mixtures with the characteristics of the binder. In this project analyzed the possibility of using fly ash in road constructions, making recipe for mixture of fly ash, stone aggregate and binder, as well as testing of mechanical and physical parametersof the mixture. The performed laboratory research as well as research in the field (in situ). Tests show that the fly ash in road construction can be used as a binder and a mineral aggregate. A mixture of ash, lime and stone aggregate (crushed stone 0-60 mm) can be used to produce lower supporting layers of pavement. The optimum composition of the mixture of ash, lime and stone aggregates are moving in the following relationships: 70% ash, 20% of the stone material and 10% lime. The project demonstrated the possibility of using ash in combination with lime and stone aggregate in various layers of roads starting from the foundation soil, then, to the lower supporting layers, provided that they are protecting the asphalt surfacing.
Keywords: fly ash; lime; connective tissue; stone aggregate; roads construction